A MIXED METHODS EVALUATION OF PROJECT TRIP: KEY FINDINGS AND EXPANSION. (20th December 2022) - Schwartz, Abby; Richman, Alice; Scott, Mallary; Liu, Haiyong; White, Weyling; Doherty, Caroline
Abstract: Project TRIP is an innovative individualized transportation program for low-income adults in rural eastern North Carolina (eNC), that aims to increase access to healthcare and reduce health disparities. This paper presents results from a 3-year grant which sought to evaluate TRIP and expand it to a neighboring eNC county. The concurrent mixed methods findings from the process/implementation, outcome/effectiveness, and economic evaluation, and qualitative interview data with TRIP stakeholders (N=40) will be presented. Findings include relationships between pre and post TRIP enrollment health data indicating improvements in health outcomes and decreases in health care utilization, including estimated costs savings of Project TRIP. Qualitative interview data will be discussed in substantiating the quantitative evaluation data. Interviews with stakeholders in the TRIP replication and expansion county site will also be presented including pilot test data in that county. The presentation will conclude with implications for sustainability and further expansion of TRIP.